Design Of Space Frame Chassis For UTeM Formula Varsity Race Car - Ashari, Muhamad Hafizullah; Mansor, Muhd Ridzuan; Mohd Rosli, Mohd Afzanizam; Akop, Mohd Zaid; Salim, Mohd Azli; Shaharuzaman, Mohd Adrinata (2012)
This paper presents the design of a space frame chassis for a new UTeM Formula Varsity race car. New single-seat open wheel race car chassis was designed as a tube chassis construction as per required in the UTeM Formula Varsity racing competition rules and regulations. Design selection method was performed to select the final concept design of tile chassis and 3D CAD model of the selected design was later constructed using CAD software. Later, load analysis used to determine the load acting on the chassis. Low carbon steel A36 was selected for the space frame chassis construction due to low cost and good structural strength properties. Theoretical structural performance of the chassis was analyzed for both bending and torsion load cases through finite eIement analysis method performed using Generative Structural Analysis module. Results from the simulation shows that the new chassis design has a minimum torsional stiffness of 4874.5 Nm.deg-' and it is 9.5% stiffer than the previous 2010 UTeM race car chassis. The new chassis was founded to have a factor of safety approximately 15.1 in static bending condition. The results show that the new chassis is capable to operate safely as per design requirements for future Formula Varsity race event.